2005
DOI: 10.1038/sj.ijir.3901303
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of inflatable penile prosthesis reservoir from the bladder

Abstract: We report a rare complication of a penile prosthesis reservoir removed from the urinary bladder in a patient with a history of radiation therapy and previous abdominal surgery. The reservoir was retrieved by open cystotomy 13 years after original placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…This seems to be an unusual combination of two typical reactions to foreign objects in the body: first, an aseptic fibrinous response to isolate and encapsulate the object, followed by erosion of the object into a hollow organ [2]. There have also been reports of penile prostheses appearing in the bladder of humans [17,18]; however, these appear to be cases of erosion into the bladder or surgical misplacement, rather than a pathway for expulsion.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be an unusual combination of two typical reactions to foreign objects in the body: first, an aseptic fibrinous response to isolate and encapsulate the object, followed by erosion of the object into a hollow organ [2]. There have also been reports of penile prostheses appearing in the bladder of humans [17,18]; however, these appear to be cases of erosion into the bladder or surgical misplacement, rather than a pathway for expulsion.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent literature review conducted in July of 2013 utilizing PubMed and Medline, we identified 37 cases of nonmechanical reservoir-related complications dating back to 1984. The most common complication was erosion of the reservoir into the bladder; which comprised 15/37 (41%) of the cases [9][10][11][12][13][14][15][16][17][18]. The most common symptom of bladder erosion was hematuria; which was found in 100% of cases.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with prior pelvic surgery, it has been well demonstrated that reservoir placement in the space of Retzius has an increased complication rate. Complications such as bladder erosion, however, exist even in low-risk patients and is the most common of all reservoir complications as demonstrated in Table 1 [9][10][11][12][13][14][15][16][17][18]39,44]. For this reason, ectopic reservoir placement has gained popularity in recent years [25,39].…”
Section: Reservoir Placement Techniquesmentioning
confidence: 99%
“…All experienced implanters have performed cystoscopy on IPP patients and seen the imprint of the reservoir of the superior bladder wall as the bladder fills with irrigation fluid. The literature is replete with case reports of bladder laceration or erosion related to reservoir placement [13–18]. Erosion seems more likely in men with a history of RRP [13,14].…”
Section: Discussionmentioning
confidence: 99%